The Antidiabetic Activity of Curry Leaves “Murraya Koenigii” on the Glucose Levels, Kidneys, and Islets of Langerhans of Rats with Streptozotocin Induced Diabetes - Al-Ani, Imad M; Santosa, Rahajoe I; Yankuzo, Muhammad H; Saxena, Anil K; Alazzawi, Khalid S (UI Scholars Hub, 2017)
Background: The aims of this study were to explore the antihyperglycemic effect of curry leaves, Murraya koenigii